Evans Syndrome: A Case Report (Bangladesh Medical Journal, 2019)
Evans syndrome, a combined clinical condition of autoimmune haemolytic anaemia (AHA) and idiopathic thrombocytopaenic purpura (ITP) and has non-specific pathogenesis. The clinical cases are extremely rare, since only 4% of AHA or ITP are incorporated with Evans. It is distinguished from differentials, such as lupus, IgA deficiency, and acquired immunodeficiency, by peripheral blood film, bone marrow, Coombs test, and coagulation profile. A case of adult female from Pabna, Bangladesh is documented in this report. She complained of high grade intermittent fever, exertional dyspnea, icteric skin and sclera. Other features included mild splenomegaly, dark urine, and profuse sweating after fever. Investigation reports were consistent with AHA and ITP, with normal coagulation and viral profile. However, the patient was treated with corticosteroids, platelet and blood transfusion. And in follow-up visits, there was a pattern of gradual decline in erythrocyte sedimentation rate (ESR) and reticulocyte count, with normalization of haemoglobin, red cell, and white cell count. No association with other diseases was found in this case.Bangladesh Med J. 2018 Jan; 47 (3): 37-40